Literasi Lingkungan melalui Program Pendidikan Pengelolaan Sampah di Masyarakat Bersama Geng Plastik Ija - Hanana Muliana; Muhammad Dahlan; Amal Akbar; Anzar Anzar; Indramini Indramini; Rahmatiah Rahmatiah; Arifuddin Arifuddin; Fajrul Khaer; Hamriani Hamriani (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2026)
Waste is a growing environmental issue, particularly in residential areas lacking effective waste management systems. This community service activity aims to improve environmental literacy through a waste management education program implemented in collaboration with the Ija Plastic Gang community. The methods used include outreach, participatory education, household-based waste management training, and ongoing mentoring. The results of the activity indicate an increase in community understanding regarding waste types, sorting methods, and simple recycling practices. Furthermore, the formation of new habits in waste management is an indicator of the program's success. The activity also fostered a sense of collective responsibility among community members toward maintaining a clean and healthy living environment. Through consistent mentoring and hands-on practice, participants demonstrated greater confidence in applying waste reduction strategies at the household level. The collaboration with the Ija Plastic Gang community proved instrumental in accelerating behavior change, as peer-to-peer engagement strengthened motivation and accountability. Ultimately, this initiative highlights the importance of integrating environmental education into community development programs to achieve long-term ecological sustainability.